2008
DOI: 10.1001/archophthalmol.2007.64
|View full text |Cite
|
Sign up to set email alerts
|

Correlations of Long-term Matrix Metalloproteinase Localization in Human Corneas After Successful Laser-Assisted In Situ Keratomileusis With Minor Complications at the Flap Margin

Abstract: To determine whether matrix metalloproteinases (MMPs) are present long-term in human corneas after successful laser-assisted in situ keratomileusis (LASIK). Methods: Eighteen postmortem corneas from 10 patients with postoperative intervals of 2 to 8 years after LASIK surgery and 4 normal control corneas from 2 patients were collected from US eye banks and processed for histologic analysis and immunolocalization with an

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 46 publications
3
10
0
Order By: Relevance
“…37,38 Matrix MMPs have also been detected at the wound margin in the cornea during wound healing after LASIK (laser-assisted in situ keratomileusis) surgery. 39 We now showed that the RAR-c agonist R667 suppressed the expression or activation of MMP-1, MMP-2, MMP-3, and MMP-9 in collagen gel cultures of corneal fibroblasts stimulated with IL1b. We have previously shown that dexamethasone and female sex hormones as well as ATRA also inhibit collagen degradation by corneal fibroblasts likely through suppression of MMP expression.…”
Section: Discussionmentioning
confidence: 80%
“…37,38 Matrix MMPs have also been detected at the wound margin in the cornea during wound healing after LASIK (laser-assisted in situ keratomileusis) surgery. 39 We now showed that the RAR-c agonist R667 suppressed the expression or activation of MMP-1, MMP-2, MMP-3, and MMP-9 in collagen gel cultures of corneal fibroblasts stimulated with IL1b. We have previously shown that dexamethasone and female sex hormones as well as ATRA also inhibit collagen degradation by corneal fibroblasts likely through suppression of MMP expression.…”
Section: Discussionmentioning
confidence: 80%
“…In a previous study, our group reported immunolocalization of MMP-9 (also known as gelatinase B) around epithelial cells trapped in the lamellar scar of post-LASIK corneas with epithelial ingrowth. 27 Matrix metalloproteinase 9 catalyzes cleavage of all types of denatured collagens as well as components of the native basement membrane. 28 It is produced in the corneal epithelium, migrating across the intact basement membrane after abrasion injury, and then disappears once regeneration is complete.…”
Section: Discussionmentioning
confidence: 99%
“…The MMP family includes more than 25 members that make up five families based on their substrate preference: collagenases (MMP-1, MMP-8, and MMP-13), stromelysins (MMP-3, MMP-10), matrilysins (MMP-7, MMP-26), gelatinases (MMP-2, MMP-9), membrane type MMPs (MPP-14 to MMP-17, MMP-24) and others 36 . Most are synthesised by resident cells, some are brought in by invading leukocytes.…”
Section: Pathology To Pathogenesismentioning
confidence: 99%
“…Most are synthesised by resident cells, some are brought in by invading leukocytes. Specific MMPs appear in specific locations within the cornea 36 , likely due to cellular and soluble factors particular to the layer. MMP changes have been described in every layer of the cornea in keratoconus.…”
Section: Pathology To Pathogenesismentioning
confidence: 99%